P74 CD161 expressing CD8+ T-cells; elusive players in viral hepatitis. (16th November 2010) - Walker, L; Kang, Y; Smith, M; Oo, Y; Barnes, E; Lauer, G; Adams, D H; Klenerman, P
Abstract : Hepatitis B (HBV) and C (HCV) -specific CD8+ T-cells are characterised by expression of the NK receptor CD161. CD8+ T cells with high levels of CD161 (CD161++) make up a mean of 12% of CD8+ T-cells in healthy controls and have distinct properties; they express the gut and liver homing chemokine receptors CCR6 and CXCR6, cytokines IL-17, IFN-y and IL-22 and have narrow TCR Vb usage (predominantly Vb 7.2 and 13), linking them to the mucosal-associated invariant T-cells of the gut. In healthy controls ∼40% of this CD161++ subset does not express the co-receptor CD8 alpha-beta (CD8ab), but the co-repressor CD8 alpha-alpha (CD8aa), yet share key functional and phenotypic features of the subset. Aim: We aimed to the study the distribution and phenotype of CD8ab and CD8aa subsets in chronic hepatitis C (cHCV) and hepatitis B (cHBV). Method: Flurochrome-labelled antibodies were used for multi-colour FACS analysis of lymphocytes in whole blood from 24 cHCV, 6 e-antigen (Ag) +ve HBV and 14 eAg−ve HBV patients and 19 healthy controls (HC). Liver infiltrating lymphocytes (LILs) (obtained from explant material; 4 HCV patients with paired PBMCs, eight alcoholic liver disease and 1 PBC) were included in the study. FACS data were analysed using FloJo software (Tree Star, Inc) and statistics were performed using PRISM (Graftpad software, Inc). Results: CD8aa cells are exclusive to the CD161++ subset in HCs, cHCV and cHBV. In cHCV and eAg−ve cHBV there is a significant reduction in the proportion of cells in the CD161++CD8+ subset compared to HCs (p≤0.05). Within the CD161++CD8+ subset there is a further reduction in the fraction of CD8aa cells in cHCV patients (18.5% vs 34.13%, p=0.0086) compared to HCs. No difference is observed in cHBV. CD8ab and CD8aa CD161+ populations are found within human LILs in HCV, ALD and PBC. The CD161+CD8aa cell subset constitute a mean of 9.9% of the total CD8+ LILs. Relative enrichment of CD161+CD8aa cells is seen in the liver of patients with cHCV compared to peripheral blood (p=0.0079). In eAg−ve cHBV a distinct CD8a+blow population can be identified within the CD161+ and CD161− subsets. These populations are not seen in HCs, eAg+ve HBV and HCV (p<0.05). Conclusion: CD161++ CD8+ T-cells are lost from the peripheral blood in cHCV and eAg−ve HBV. Maintenance of this subset in eAg+ve HBV may reflect immuno-tolerance to virus at this stage of infection. In chronic HCV there is a relative enrichment of the CD161+CD8+ subset in LILs, indicating recruitment to and retention in the liver. The role of these cells in health, immunity and disease outcome in viral hepatitis requires further study. The emergence of a CD161+/CD161-CD8a+blow subset in eAg−ve HBV may reflect activation or exhaustion of these cells; their phenotype and function requires investigation.